Long-term grazing exclusion enhances soil carbon and nitrogen stocks in tropical dry forests of southern Ecuador - Jiménez, Leticia; Ramón, Pablo; Sarango, Jhonattan; Burneo, Juan Ignacio; Gusmán, Johana; Gusmán-Montalván, Elizabeth (Frontiers in Soil Science, 2025)
Anthropogenic activities, particularly agriculture and cattle ranching, transform forest ecosystems and alter soil properties in tropical dry forests. This study quantified changes in carbon (C) and nitrogen (N) stocks and soil nutrient composition across three land use types: excluded forest (EF - protected from grazing for 8 years), non-excluded pasture (NEP), and maize cropland (Cr) in southern Ecuador. We established three 1-ha plots per land use type and collected 225 soil samples (0–10 cm depth) for physicochemical analysis using standard methods including loss-on-ignition for C determination and Kjeldahl method for N analysis. Carbon stocks were significantly higher in excluded forest (18.09 Mg/ha) compared to cropland (17.67 Mg/ha, p<0.05), while nitrogen stocks were elevated in cropland (2.66 Mg/ha) versus excluded forest and pasture (2.04 Mg/ha). Soil texture, electrical conductivity, phosphorus, and potassium concentrations differed significantly among land use types (p<0.05). Excluded forests showed the highest calcium and magnesium concentrations, while croplands exhibited elevated phosphorus and potassium levels due to fertilization practices. These findings demonstrate that grazing exclusion enhances soil carbon sequestration in tropical dry forests and highlight the importance of forest conservation strategies for climate change mitigation.